2007
DOI: 10.1007/s10658-007-9215-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine ammonia lyase activity in chilli CM-334 infected by Phytophthora capsici and Nacobbus aberrans

Abstract: We tested the hypothesis that PAL activity in chilli plants CM-334 inoculated with Nacobbus aberrans (Na) alone or in combination with Phytophthora capsici (Pc), is lower than in those inoculated only with Pc. At 21 days after nematode inoculation, inoculated plants showed a significant (P<0.01) reduction of 48% in PAL activity compared to those non-inoculated in two separate experiments. In two other tests, where plants were inoculated with the oomycete 21 days after inoculation with the nematode, PAL activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The lower PAL activity in CM334 plants inoculated with Na alone or in combination with Pc was in agreement with the results reported by Godínez-Vidal et al (2008), who suggested that, in a similar way to M. incognita, N. aberrans could alter the patterns of genetic expression in its host, including repressing the expression of PAL, as previously reported in compatible plant-nematode interactions (Goddijn et al 1993;Baldridge et al 1998). Inhibition of the gene PALwhich codes for PAL biosynthesis, a key enzyme in defense mechanisms (Cahill and McComb 1992;Fernández-Pavia 1997;Boudet 2000;Dixon et al 2002;Shadle et al 2003)-would favor infection and reproduction of the nematode.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The lower PAL activity in CM334 plants inoculated with Na alone or in combination with Pc was in agreement with the results reported by Godínez-Vidal et al (2008), who suggested that, in a similar way to M. incognita, N. aberrans could alter the patterns of genetic expression in its host, including repressing the expression of PAL, as previously reported in compatible plant-nematode interactions (Goddijn et al 1993;Baldridge et al 1998). Inhibition of the gene PALwhich codes for PAL biosynthesis, a key enzyme in defense mechanisms (Cahill and McComb 1992;Fernández-Pavia 1997;Boudet 2000;Dixon et al 2002;Shadle et al 2003)-would favor infection and reproduction of the nematode.…”
Section: Discussionsupporting
confidence: 91%
“…The lower contents of chlorogenic acid in resistant (CM334) and susceptible (J. E. Parker) plants inoculated with N. aberrans as compared to the non-inoculated ones, along with the fact that PAL activity was lower in nematode-inoculated plants compared to those noninoculated, further supports the idea that in compatible interactions the nematode interferes with the plant defence mechanisms-most likely those related to the phenylpropanoid pathway- (Edens et al 1995;Wuyts et al 2006a;Godínez-Vidal et al 2008). Our results also reinforce the idea that, in the incompatible interaction M. incognita-CM334, the chlorogenic acid synthesized through the phenylpropanoids route might play an important role in the resistance to this nematode, as previously reported by Pegard et al (2005); such resistance was expressed as a classical hypersensitive response.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations